TRICHOTOSIA GABRIEL-ASEMIANA (ORCHIDACEAE), A NEW SPECIES FROM TAMBRAUW, WEST PAPUA PROVINCE, INDONESIA - Yasper Michael Mambrasar; ANDRÉ SCHUITEMAN (REINWARDTIA, 2017)
MAMBRASAR, Y. M. & SCHUITEMAN, A. 2017. A new species of Trichotosia (Orchidaceae: Epidendroideae: Podochileae) from Tambrauw, Papua New Guinea, Indonesia. Reinwardtia 16(2): 107-110. - Trichotosia gabriel-asemiana Mambrasar & Schuiteman. Its description and illustration was presented.